Age Scale for Assessing Activities of Daily Living - Figueroa, Rafael; Seino, Satoshi; Yabushita, Noriko; Okubo, Yoshiro; Osuka, Yosuke; Nemoto, Miyuki; Jung, Songee; Tanaka, Kiyoji (International Journal of Statistics in Medical Research, 2015)
The purpose of this study was to develop an age scale for assessing activities of daily living (ADL) among community-dwelling adults aged 75 years or older. Participants were 1006 older Japanese: 312 men (79.6 ± 4.3 years) and 694 women, (79.9 ± 5.5 years). Participants completed a battery of 8 performance tests related to ADL and the Barthel index (BI) questionnaire. Spearman rank-order correlation analysis was applied to obtain the correlation of the 8 ADL performance tests with the total BI score. Three variables were high rank-order correlated with BI, secondly those items were subjected to the principal component analysis. The weighted combination of the principal component scores was summed. Resulting in an ADL score (ADLS), women = 0.075 X1 – 0.082 X2 – 0.063 X3 + 0.124, men = 0.051 X1 – 0.105 X2 – 0.099 X3 + 0.249, where X1 = hand-grip strength, X2 = timed up and go, X3 = five-chair sit to stand. Individual ADLS was transformed to an ADL age scale (ADLA). The estimation was – 5.493 ADLS + 79.90 for women, and – 4.272 ADLS + 79.57 for men. Due to the distortion at the regression edges, the equation was corrected as suggested by Dubina et al. ADLA women after correction was = 0.447 (chronological age: CA) – 5.49ADLS + 44.17, men = 0.519CA – 4.27ADLS + 38.26. ADLA can be used to identify or monitor the characteristics of the ADL levels of physical abilities in older Japanese aged 75 years or older.